Association between alcohol and drug use and arrest for driving under the influence after crash involvement in a rural area of Norway: a case–control study. Issue 1 (3rd January 2019) - Jamt, Ragnhild Elén Gjulem; Gjerde, Hallvard; Romeo, Giovanni; Bogstrand, Stig Tore
Abstract : Objectives: The rate of deaths caused by road traffic crashes is particularly high in rural areas. It has been hypothesised that one factor that may contribute is differences in patterns of alcohol use. The aim was to compare the prevalence of psychoactive substances among crash-involved drivers arrested for suspicion of driving under the influence (DUI) who are tested for alcohol and drugs and recent random drivers in a rural area. Furthermore, we investigated the association between traffic crashes and driving after using alcohol, illicit or medicinal drugs either alone or in combination. Methods: A case–control study was carried out in which the case group consisted of crash-involved drivers arrested for suspicion of DUI from 2000 to 2015. This group was compared with a control group of randomly selected drivers recruited to a roadside survey in normal traffic from 2014 to 2015. The case group consisted of 612 individuals (542 men and 70 women) and the control group of 3027 individuals (2099 men and 927 women). Drug and alcohol screening was performed on blood samples from the cases and samples of oral fluid from the controls. Results: The proportion of psychoactive substances was 81.7% among cases and 1.6% among the controls. The prevalence of combinations of psychoactive substances was 18% among the cases and 0.3% among the controls. The multivariate regression model analysis identified significant drug interactions. Conclusion: The prevalence of alcohol and drugs was high among the crash-involved drivers arrested for suspicion of DUI by the police. In contrast to earlier published research combinations of different psychoactive substances did not increase the OR for traffic crash involvement more than the single drug with highest OR. The statistical methodology presented in this study should be allied in future studies with greater statistical power to confirm these findings.